Design and Development of 35–4.4 GHz Inset-Fed 2 × 2 Phased Array Microstrip Patch Antenna for Intentional Electromagnetic Interference Testing - John Joshua O. Gutierrez; Jervin D. Louis; Jennifer C. Dela Cruz (Engineering Proceedings, 2025)
Communication devices are frequency-operating electronics equipment that utilizes analog modulation, frequency modulation, shortwave frequency, and even higher frequencies in telecommunications. We designed an antenna to transmit interfering frequencies for testing equipment and components based on the effects and conditions of achieving electromagnetic interference. Ansys 2024 was used to design the 35 to 4.4 GHz 2 × 2 patch antennas and simulate the response using a sample frequency of 35 MHz to determine the antenna’s polarization. The polarization was circular, in contrast to the results of the phases Phi and Theta observed in the radial field 3D polar plot, which are completely out of phase and different in magnitude by 5.4 in Phi and 5402.01 in Theta. The measurements from Ansys were congruent to the 2D model dimensions in AutoCAD 2024. The antenna was fabricated under a double-layered photosensitive FR-4 copper board. The antenna connected to the signal generator ADF 4351 effectively was interfered with by a frequency near the actual frequency with a maximum distance of 7.5 m in a room. The frequencies that interfered were from 91.5 to 102.7 MHz. Strong electromagnetic waves for interference disrupted frequency-operating devices due to high signal power achieving destructive interference.